2014
DOI: 10.1111/are.12651
|View full text |Cite
|
Sign up to set email alerts
|

The suitable dose of gamma irradiation on soybean meal as a fish meal substitute in diets for golden pompano (Trachinotus ovatus)

Abstract: A 5‐week feeding trial was conducted to assess the effect of gamma ray irradiation treatment on soybean meal as a fish meal substitute in diets for golden pompano (Trachinotus ovatus). A diet containing 32% fish meal served as a reference (C), and 75% of the fish meal was replaced by soybean meal that either received no gamma ray irradiation (R0) or was irradiated with gamma ray at a dose of 5 (R5), 10 (R10), 15 (R15), 30 (R30) or 60 (R60) kGy respectively. All the diets were formulated to contain 46% crude pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Deficiency of some essential amino acids, such as Met and Lys, has been recognized as one of the factors limiting dietary fish meal replacement with terrestrial animal and plant ingredients (Glencross, Booth, & Allan, ). In some studies, however, supplementation of crystalline Met and Lys could not increase the level of fish meal replacement with soybean meal in diets for Japanese sea bass and golden pompano (Wu, Ren, Qin, Han, & Wang, ; Zhang et al., ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of some essential amino acids, such as Met and Lys, has been recognized as one of the factors limiting dietary fish meal replacement with terrestrial animal and plant ingredients (Glencross, Booth, & Allan, ). In some studies, however, supplementation of crystalline Met and Lys could not increase the level of fish meal replacement with soybean meal in diets for Japanese sea bass and golden pompano (Wu, Ren, Qin, Han, & Wang, ; Zhang et al., ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al . () reported that γ‐ray irradiation on SBM can significantly improve the growth of golden pompano fed a diet with fish meal replaced by SBM. In the present study, weight gain was higher in fish fed diets SM30 or SC30 than in fish fed diets SM or SC.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al . () considered that the mechanisms for enhanced SBM inclusion in fish diet after γ‐ray irradiation might be due to the inactivation of undesirable proteins. The SDS‐PAGE electrophoretion indicated that the level of the protein subunits with molecular weight >6.5 kDa in SBM and SPC declined after γ‐ray irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Wu et al. () reported that no significant differences were found in the HSI between the golden pompano ( Trachinotus ovatus ) fish fed fish meal (FM)‐based control diet and diet where 75% FM was replaced by irradiated (15 kGy) SBM. Lower HSI and ISI values exhibited by the fish of T15 and T20 groups might be due to the effect of PEs and phytic acid as reported by Kumar, Makkar, Amselgruber, et al.…”
Section: Discussionmentioning
confidence: 99%